Vídeo educativo sobre osteoartrite de joelho e quadril para pessoas idosas, em isolamento social pela pandemia da COVID-19 - Montenegro, Renata Moreira (2023)
Introduction: with social isolation due to the COVID-19 pandemic, the general population and especially the elderly, considered more vulnerable to infection, were subjected to sudden changes in the routine of their activities. It is observed that elderly people with knee and hip osteoarthritis had consequences for the clinical presentation of their disease, compromising regular treatment and quality of life. Objectives: to understand scientific evidence on knee and hip osteoarthritis in elderly people; verify the impact of social isolation due to Covid-19 on elderly people with osteoarthritis; create an educational guidance video for elderly people with osteoarthritis, in social isolation due to the COVID-19 pandemic. Method: this is a methodological study with a qualitative approach, structured in three stages: the first involves finding out scientific evidence on knee and hip osteoarthritis in elderly people; In the second stage, a semi-structured interview with a qualitative approach was carried out with 24 elderly people with osteoarthritis, treated in the city of João Pessoa/Paraíba/Brazil. Data were collected from a semi-structured interview and analyzed using the Descending Hierarchical Classification; the third stage included the creation of an educational video about osteoarthritis for elderly people in social isolation due to the COVID-19 pandemic. Results: in the scoping review, overweight and low rates of physical activity were observed to have a greater impact on the progression of knee and hip osteoarthritis. The results of the interviews show that elderly people with knee and hip osteoarthritis undergoing treatment associated the pandemic with a significant impact on their lives resulting from the need for social isolation and the interruption of their physical activities, as a justification for the worsening of their pain as a result. limitation of movement and increased use of analgesics. Hence, an educational guidance video was created for elderly people with osteoarthritis, in social isolation due to the COVID-19 Pandemic. Final Considerations: we sought to highlight in the literature the modifiable variables that impact the progression of knee and hip osteoarthritis; highlighting the impact of social isolation due to Covid-19 according to elderly people with knee and hip osteoarthritis and the construction of an educational video on knee and hip osteoarthritis for elderly people, in social isolation due to the COVID-19 pandemic, reinforcing the importance of remain active, even during periods of isolation and staying at home for their functional health and reduction of clinical symptoms.